Zooming Into the Ecosystem: Agency and Politics Around Open Data Platforms in Lyon and Berlin - Slobodova, Olga; Becker, Sören (Frontiers in Sustainable Cities, 2020)
Open data platforms provide free access to datasets in key areas of urban development. Often provided by the local state, open data platforms constitute a part of smart city strategies worldwide, serving different, potentially contradictory aims, i.e. fostering economic development, enhancing transparency of urban governance and reshaping the relation between citizens and the state. While benefits of open data are often highlighted, recent research has pointed out to open data initiatives failing to account for and include the ecosystem of urban actors and their interests. Instead, open data platforms are embedded in complex networks of actors and institutions, and consequently form both an object and an instrument of urban governance. Our interest lies in understanding how open data platforms are coproduced by different actors based on their conception of open data. Thus, we theorise the development of open data initiatives through a dynamic approach to agency focussing on the strategies of different actor groups shaping open data initiatives and platforms, in specific governance contexts that define barriers and windows of opportunity. Empirically, our paper will analyse the development and governance of open data initiatives and platforms in the cities of Lyon and Berlin. Departing from the initial steps for setting open data on the agenda, we will provide a process-based perspective unpacking actor strategies and agency to shape open data policies, concrete initiatives and platform design. The analysis is based on tracing the development processes and on interviews with representatives of the administration, open data initiatives and civil society. Our analysis identified a narrowing down of open data initiatives to objectives of economic development and efficient administration, despite the existence of broader visions on open data among other actors. This can be traced back to the impact of shifts in the urban governance contexts and high salience of personnel, financial and technical resources for defining the dominant conception of open data.